Lithium cobalt oxide composite material and preparation method and application thereof

By using O2 phase lithium cobalt oxide doped with M elements in the positive electrode material of lithium ion battery and covering the N element oxide layer, the problem of poor cycling stability of O3 phase lithium cobalt oxide at high potential is solved, and better cycling performance and magnification characteristics are achieved.

CN119650618APending Publication Date: 2025-03-18ZHEJIANG HUAYOU COBALT CO LTD +2
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202411630475.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Conventional O3-phase lithium cobalt oxide is poor in cycling stability as the positive electrode material of lithium-ion batteries at high potentials.

Method used

The O2 phase lithium cobalt oxide doped with M element is used as the core body, and an oxide coating layer containing N elements is coated on its surface, which is achieved by fusion coating treatment.

Benefits of technology

The cycling performance of O2 phase lithium cobalt oxide at high voltage is improved, structural phase change is suppressed, and side reactions between the material and the electrolyte are reduced, thereby improving the cycling stability and magnification characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650618A_ABST
    Figure CN119650618A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and provides a lithium cobalt oxide composite material which comprises a core body and a coating layer coating the core body, the core body comprises O2-phase lithium cobalt oxide, and the O2-phase lithium cobalt oxide is doped with an element M; the coating layer comprises an oxide containing an N element; the M element comprises at least one of Al, Mg, W, Ti, La, Zr, Ni, Mn and Y; n comprises at least one of Al, Mg, Y, W, Nb, La, Zr, Ti and P. The lithium cobalt oxide composite material provided by the invention is used as a positive electrode material of a lithium ion battery, and the cycling stability of the lithium ion battery under high potential is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lithium-ion batteries, and in particular relates to a lithium cobalt oxide composite material and a preparation method and application thereof. Background Art

[0002] Lithium-containing layered transition metal oxide cathode material LiCoO 2 It was first reported by John B.Goodenough et al. in 1980. LiCoO 2 The layered structure is Li + It provides a 2D diffusion channel and has the advantages of large specific capacity, high voltage, and good cycle performance, and has been widely studied and applied. 2 The space group is R-3m, Li + and Co 3+ Layers are arranged alternately in a cubic close-packed O 2- In the octahedral positions formed, LiO6 and CoO6 octahedra are stacked with shared edges, and the arrangement order of the O layer is ABCABC, which belongs to the O3 phase.

[0003] O3 phase LiCoO 2 The theoretical capacity is as high as 274 mAh / g, which has a very high volume energy density, but LiCoO 2 The actual capacity release is closely related to the charging voltage. For example, when charged to 4.4V, it has a specific capacity of 170mAh / g and a volume energy density of 2820.3Wh / L, which is comparable to the current high-nickel ternary material 811. To further improve LiCoO 2 The capacity and energy density of LiCoO 2 Therefore, the researchers conducted a study on the high-voltage LiCoO 2 With various theoretical studies, coating and doping modifications, LiCoO 2 The voltage is gradually increased, but when charged to 4.5V and above, LiCoO 2 The capacity decay mechanism in organic electrolyte is more complicated, which is not only related to the crystal structure and electronic structure of the material itself, but also to the type of electrolyte and the properties of the interface. The O3-H1-3-O1 phase transition that begins at 4.5V reduces the reversibility of the slip phase transition of the CoO2 layer, and the particles undergo a c-axis contraction of more than 3%. At the same time, due to the overlap of the top of the Co3+ / 4+:3d energy band and the O2-:2p energy band, LiCoO 2 When charged to a higher potential, O 2- Will provide charge compensation and cause oxidation reaction, O 2It will be released from the lattice, causing damage to the material. In addition, some researchers have found that when charged to a higher potential, LiCoO 2 The interface is unstable and will generate a spinel phase with low electrochemical activity. In addition, some researchers believe that some solvents in organic electrolytes will react with LiCoO 2 The surface of LiCoO 2 The interface changes or even dissolves. Summary of the invention

[0004] The purpose of the present application is to provide a lithium cobalt oxide composite material and a preparation method and application thereof, aiming to solve the technical problem that conventionally using O3 phase lithium cobalt oxide as a positive electrode material for lithium-ion batteries has poor cycle stability at high potentials.

[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0006] In a first aspect, the present application provides a lithium cobalt oxide composite material, comprising a core body and a coating layer coated on the core body, wherein the core body comprises O2 phase lithium cobalt oxide, and the O2 phase lithium cobalt oxide is doped with an M element; the coating layer comprises an oxide containing an N element;

[0007] The M element includes at least one of Al, Mg, W, Ti, La, Zr, Ni, Mn and Y;

[0008] The N includes at least one of Al, Mg, Y, W, Nb, La, Zr, Ti and P.

[0009] In a second aspect, the present application provides a method for preparing a lithium cobalt oxide composite material, comprising:

[0010] The O2 phase lithium cobalt oxide material doped with the M element is mixed with the coating material to perform a fusion coating process to obtain a lithium cobalt oxide composite material; wherein,

[0011] The M element includes at least one of Al, Mg, W, Ti, La, Zr, Ni, Mn and Y;

[0012] The coating material includes an oxide containing N element, and the N includes at least one of Al, Mg, Y, W, Nb, La, Zr, Ti and P.

[0013] In a third aspect, the present application provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active layer stacked and bonded to at least one surface of the positive electrode current collector, wherein the positive electrode active layer comprises the lithium cobalt oxide composite material provided in the first aspect and / or the lithium cobalt oxide composite material prepared by the preparation method provided in the second aspect.

[0014] In a fourth aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet provided in the third aspect.

[0015] Compared with the prior art, the beneficial effects of this application are:

[0016] The lithium cobalt oxide composite material provided in the first aspect of the present application adopts an O2 phase lithium cobalt oxide doped with an M element as the core body, and the O2 phase lithium cobalt oxide has a higher structural stability. By doping with the M element, the structural stability of the O2 phase lithium cobalt oxide can be further enhanced, and its cycle performance under high voltage can be improved, and the structural phase change during high voltage charging and discharging can be suppressed, and the side reaction between the material and the electrolyte can be reduced, thereby improving the cycle stability and rate characteristics of the battery. The surface of the core body is coated with an oxide coating layer containing the N element to form a protective structure, which can reduce the direct contact between the lithium cobalt oxide composite material and the electrolyte when used as a positive electrode material, thereby suppressing side reactions and improving the cycle stability of the battery. Therefore, the cycle stability of the lithium cobalt oxide composite material of the embodiment of the present application at high potential is greatly improved.

[0017] The second aspect of the present application provides a method for preparing a lithium cobalt oxide composite material, which comprises mixing an O2 phase lithium cobalt oxide material doped with the M element with a coating material and then coating the mixture using a fusion coating treatment. The fusion coating treatment does not require high-temperature calcination, but rather achieves fusion coating at a relatively low temperature through physical methods, thereby maintaining the structure of the O2 phase lithium cobalt oxide and forming a coating layer on the surface. The preparation method is simple and easy and can be used for industrial large-scale production.

[0018] The positive electrode sheet provided in the third aspect of the present application has good electrochemical properties, such as a more stable structure and better cycle stability under high voltage, because it adopts the lithium cobalt oxide composite material provided in the present application as the positive electrode active layer material.

[0019] The lithium-ion battery provided in the fourth aspect of the present application has good electrochemical properties, such as a more stable structure and better cycle stability under high voltage, because it adopts the positive electrode sheet provided by the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0021] Figure 1 This is a CP-EPMA image of the cross section of the lithium cobalt oxide composite material prepared in Example 1 of the present application;

[0022] Figure 2 This is a CP-EPMA image of the Al element in the cross section of the lithium cobalt oxide composite material prepared in Example 1 of the present application;

[0023] Figure 3 This is the XRD diagram of the lithium cobalt oxide composite material prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0024] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0025] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0026] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0027] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0028] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0029] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0030] In a first aspect of an embodiment of the present application, a lithium cobalt oxide composite material is provided, comprising a core body and a coating layer coated on the core body, wherein the core body comprises O2 phase lithium cobalt oxide, and the O2 phase lithium cobalt oxide is doped with an M element. The coating layer comprises an oxide containing an N element. The M element comprises at least one of Al, Mg, W, Ti, La, Zr, Ni, Mn and Y. N comprises at least one of Al, Mg, Y, W, Nb, La, Zr, Ti and P.

[0031] O2 phase lithium cobalt oxide refers to lithium cobalt oxide with a specific crystal structure. The layered arrangement order of cobalt and lithium is CoO2-Li-Li-CoO2, while in O3 phase lithium cobalt oxide, the arrangement order is CoO2-Li-CoO2-Li. Therefore, compared with O3 phase lithium cobalt oxide, O2 phase lithium cobalt oxide has a different spatial arrangement, and can still maintain a stable crystal structure at a higher delithiation state. The CoO6 octahedron in O2 phase lithium cobalt oxide has a stronger Co-O bond, which enhances the structural stability to resist proton attack and prolongs its cycle life in aqueous electrolytes. Moreover, the C axis of O2 phase lithium cobalt oxide is larger, so it has a higher discharge capacity and better cycle stability. In addition, O2 phase lithium cobalt oxide undergoes a reversible phase transition during the cycle process and will not be converted into thermodynamically stable O3 phase lithium cobalt oxide or spinel phase. Therefore, the lithium cobalt oxide composite material provided in the embodiment of the present application adopts an O2 phase lithium cobalt oxide doped with an M element as the core body. By doping with the M element, the structural stability of the O2 phase lithium cobalt oxide can be enhanced, and its cycle performance under high voltage can be improved, and the structural phase change during high voltage charging and discharging can be suppressed, and the side reaction between the material and the electrolyte can be reduced, thereby improving the cycle stability and rate characteristics of the battery. The surface of the core body is coated with an oxide coating layer containing the N element to form a protective structure, which can reduce the direct contact between the lithium cobalt oxide composite material and the electrolyte, thereby suppressing side reactions and improving the cycle stability and safety of the battery. Therefore, the stability of the lithium cobalt oxide composite material of the embodiment of the present application is greatly improved at high potential.

[0032] In some embodiments of the present application, the molar ratio of lithium element to cobalt element in the lithium cobalt oxide composite material is 0.9-1.

[0033] In the lithium cobalt oxide composite material, the molar ratio of lithium element to cobalt element is ensured to be 0.9-1, which can ensure that the lithium cobalt oxide composite material has a high discharge capacity and good cycle stability. When used as a positive electrode material in lithium-ion batteries, it can be used directly without the need for negative electrode lithium supplementation treatment.

[0034] In some embodiments of the present application, the chemical formula of the lithium cobalt oxide composite material is Li x Na y Co 1-m M m N n O 2 , M includes at least one of Al, Mg, W, Ti, La, Zr, Ni, Mn and Y, and N includes at least one of Al, Mg, Y, W, Nb, La, Zr, Ti and P. Wherein, 0.9≤x≤1, 0≤y≤0.1, 0<m≤0.1, 0<n≤0.1, and 0.9≤x / (1-m)≤1.0.

[0035] According to the general chemical formula of the lithium cobalt oxide composite material, it can be seen that the lithium cobalt oxide composite material is doped with the M element, and the molar fraction m of the M element and the molar fraction (1-m) of the Co element add up to 1, that is, the M element is doped at the Co site, which can improve the charge and discharge capacity and cycle stability of the lithium cobalt oxide composite material. In addition, 0.9≤x / (1-m)≤1.0, that is, the molar ratio of the lithium element to the cobalt element is greater than or equal to 0.9 and less than or equal to 1, which can ensure that the lithium cobalt oxide composite material has a high discharge capacity and good cycle stability, and can be used directly when applied to lithium-ion batteries as a positive electrode material without the need for negative electrode lithium supplementation.

[0036] In some embodiments, the main X-ray diffraction peak of O2 phase lithium cobalt oxide is located at 18.6±0.1°.

[0037] X-ray diffraction (XRD) is a commonly used material structure analysis technique. XRD can determine the crystal structure of O2-phase lithium cobalt oxide by analyzing the diffraction pattern of the material to X-rays. In the XRD spectrum, the main peak corresponds to the specific spacing between atomic planes in the O2-phase lithium cobalt oxide crystal.

[0038] The main X-ray diffraction peak of O2 phase lithium cobalt oxide is at 18.6±0.1°, which can confirm that the O2 phase lithium cobalt oxide in the embodiment of the present application belongs to the O2 phase structure, and can indicate that the O2 phase lithium cobalt oxide has a specific crystal structure. Co atoms and O atoms form CoO6 octahedrons through covalent bonds. The CoO6 octahedron in the O2 phase lithium cobalt oxide has a stronger Co-O bond, thereby enhancing the structural stability to resist proton attack and prolonging its cycle life in aqueous electrolytes.

[0039] In some embodiments, the coating layer has a thickness less than 1 micron. For example, the coating layer may have a thickness of 0.01 micron, 0.05 micron, 0.1 micron, 0.3 micron, 0.5 micron, 0.8 micron, 0.9 micron, or any value between the above adjacent values.

[0040] The thickness of the coating layer is controlled to be less than 1 micron so as not to cause excessive interface resistance of the lithium cobalt oxide composite material, thereby preventing the subsequent capacity release performance of the lithium ion battery from being affected.

[0041] In some embodiments, the particle size of the core body is 5 to 20 microns. For example, the particle size of the core body can be 5 microns, 8 microns, 10 microns, 12 microns, 15 microns, 18 microns, 20 microns, or any value between the above adjacent values.

[0042] By controlling the particle size of the core, the electrochemical performance of the lithium cobalt oxide composite material can be guaranteed.

[0043] A second aspect of the embodiment of the present application provides a method for preparing a lithium cobalt oxide composite material, comprising:

[0044] The O2 phase lithium cobalt oxide material doped with the M element is mixed with the coating material for fusion coating treatment to obtain a lithium cobalt oxide composite material. The M element includes at least one of Al, Mg, W, Ti, La, Zr, Ni, Mn and Y. The coating material includes an oxide containing the N element, and N includes at least one of Al, Mg, Y, W, Nb, La, Zr, Ti and P.

[0045] In conventional O3 phase lithium cobalt oxide, the coating method is to coat by mixing the O3 phase lithium cobalt oxide core and the coating material and then calcining at high temperature (generally > 600°C). However, O2 phase lithium cobalt oxide has the characteristic of low phase transition temperature, and it will transform to O3 phase above 280°C. Therefore, conventional O3 lithium cobalt oxide coating technology is difficult to achieve effective coating of O2 phase lithium cobalt oxide.

[0046] Based on the above, the preparation method of the lithium cobalt oxide composite material provided in the embodiment of the present application realizes a fusion coating treatment by mixing an O2 phase lithium cobalt oxide material doped with the M element with a coating material. The fusion coating treatment does not require high-temperature calcination, but instead realizes fusion coating at a relatively low temperature through physical methods, thereby maintaining the structure of the O2 phase lithium cobalt oxide and forming a coating layer on the surface.

[0047] Specifically, the fusion coating process is a process in which the O2-phase lithium cobalt oxide material doped with the M element and the coating material are mixed by high-speed rotation in a high-speed mixing device, and friction heat is released during the mixing process. The high-speed mixing device may be a planetary stirring vacuum degassing machine.

[0048] In some embodiments, the coating material includes at least one of aluminum oxide, magnesium oxide, lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanate (LLTO), and lithium aluminum titanium phosphate (LATP).

[0049] Among the above-mentioned coating materials, aluminum oxide and magnesium oxide are commonly used oxide materials, which are easy to obtain from the market and can be obtained as nano-scale materials, making it easier to achieve fusion coating. LLZO, LLTO and LATP are all fast ion conductors, which are conducive to interfacial lithium ion transmission.

[0050] In some embodiments, the mass ratio of the coating material to the O2-phase lithium cobalt oxide material containing the M element is (0.2-0.8): 100. For example, the mass ratio of the coating material to the O2-phase lithium cobalt oxide material containing the M element can be 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, or any value between the above adjacent values.

[0051] By controlling the mass ratio of the coating material and the O2 phase lithium cobalt oxide material containing the M element, the thickness of the coating layer in the final lithium cobalt oxide composite material can be controlled, thereby ensuring that the lithium cobalt oxide composite material plays an interface protection role without a significant decrease in capacity, thereby improving the first efficiency and cycle stability.

[0052] In some embodiments, the rotation speed of the fusion coating process is 1500r / min-5000r / min, and the time of the fusion coating process is 5min-30min. For example, the rotation speed of the fusion coating process can be 1500r / min, 1800r / min, 2000r / min, 2500r / min, 3000r / min, 4000r / min, 5000r / min, or any value between the above adjacent values. The time of the fusion coating process can be 5min, 8min, 10min, 15min, 20min, 25min, 30min.

[0053] By controlling the rotation speed of the fusion coating treatment at 1500r / min-5000r / min and the time of the fusion coating treatment at 5min-30min, the effect of full fusion coating can be achieved without causing the O2 phase structure to transform into the O3 phase structure.

[0054] In some embodiments, the steps of preparing the O2-phase lithium cobalt oxide material doped with the M element include:

[0055] The sodium source, the cobalt source and the M element doping source are mixed and then sintered to obtain a P2Na precursor.

[0056] The P2Na precursor is mixed with the first lithium source and then subjected to molten salt ion exchange treatment to obtain an O2 phase lithium cobalt oxide material doped with the M element.

[0057] Using a sodium source, a cobalt source and an M element doping source as raw materials, a P2Na precursor is synthesized by a sintering method, and then an O2 phase lithium cobalt oxide material doped with the M element is synthesized through a molten salt ion exchange treatment.

[0058] In some embodiments, the sodium source includes at least one of sodium carbonate, sodium hydroxide, and sodium bicarbonate.

[0059] The above-mentioned sodium source raw materials are easy to obtain from the market and are convenient for controlling the reaction.

[0060] In some embodiments, the cobalt source includes at least one of cobalt trioxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt sulfate, and cobalt oxyhydroxide.

[0061] The above-mentioned cobalt source raw materials are easy to obtain from the market and are convenient for controlling the reaction.

[0062] In some embodiments, the M element doping source includes Al 2 O 3 、MgO、WO 3 、TiO 2 ,La 2 O 3 、ZrO 2 、NiO、MnO 2 and Y 2 O 3 At least one of them.

[0063] The above-mentioned M element doping source is easy to obtain from the market, and the use of the above-mentioned M element doping source for doping can improve the discharge capacity of the product.

[0064] In some embodiments, the molar ratio of sodium ions in the sodium source to cobalt ions in the cobalt source is (0.6-1.0): 1. In some embodiments, the molar ratio of sodium ions in the sodium source to cobalt ions in the cobalt source is (0.7-0.75): 1. In some embodiments, the molar ratio of sodium ions in the sodium source to cobalt ions in the cobalt source can be 0.6: 1, 0.7: 1, 0.75: 1, 0.8: 1, 0.9: 1, 1.0: 1, or any value between the adjacent values ​​above.

[0065] When the molar ratio of sodium ions in the sodium source to cobalt ions in the cobalt source is controlled within the above ratio range, the synthesized P2Na precursor is relatively pure and has a rounded and complete morphology.

[0066] In some embodiments, the molar ratio of the sodium source to the M element doping source is 1:(0.001-0.02). For example, the molar ratio of the sodium source to the M element doping source is 1:0.001, 1:0.005, 1:0.01, 1:0.015, 1:0.02, or any value between the above adjacent values.

[0067] The molar ratio of the sodium source to the M element doping source is selected within the above ratio range, which makes it easier to form an O2 phase lithium cobalt oxide material doped with the M element.

[0068] In some embodiments, the sintering temperature is 700°C-900°C, and the sintering time is 8h-30h. In some embodiments, the sintering temperature is 700°C, 750°C, 780°C, 800°C, 850°C, 880°C, 900°C, or any value between the above adjacent values. The sintering time is 8h, 10h, 13h, 15h, 18h, 22h, 25h, 30h, or any value between the above adjacent values.

[0069] Controlling the temperature and time of the sintering treatment within the above range is conducive to the normal progress of the reaction.

[0070] In some embodiments, the sintering process is specifically to increase the temperature to 700°C-900°C at a heating rate of 1°C / min-10°C / min, keep the temperature and sinter for 8h-30h, and then cool to room temperature in the furnace.

[0071] In some embodiments, the first lithium source includes at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium acetate, and lithium hydroxide.

[0072] The above-mentioned lithium source materials are easy to obtain from the market and are conducive to the control of the reaction.

[0073] In some embodiments, the molar ratio of lithium ions in the first lithium source to sodium ions in the P2Na precursor is (1-20): 1. In some embodiments, the molar ratio of lithium ions in the first lithium source to sodium ions in the P2Na precursor is 1:1, 2:1, 6:1, 9:1, 11:1, 15:1, 17:1, 20:1, or any value between the above adjacent values.

[0074] The molar ratio of lithium to sodium (Li / Na) can reflect the power of ion exchange, and the Li / Na ratio within the above range is conducive to the normal progress of the reaction.

[0075] In some embodiments, the temperature of the molten salt ion exchange treatment is 180°C-300°C, and the time of the molten salt ion exchange treatment is 0.5h-12h. In some embodiments, the temperature of the molten salt ion exchange treatment is 180°C, 200°C, 220°C, 250°C, 270°C, 300°C, or any value between the above adjacent values. The time of the molten salt ion exchange treatment is 0.5h, 1h, 3h, 5h, 7h, 9h, 10h, 12h, or any value between the above adjacent values.

[0076] The above-mentioned temperature range and time range of the molten salt ion exchange treatment are conducive to the normal progress of the reaction, and the above-mentioned temperature range will not cause the O2 phase structure to transform into the O3 phase structure.

[0077] In some embodiments, the molten salt ion exchange treatment is specifically heated to 180-300°C at a heating rate of 1°C / min-10°C / min and kept warm for 0.5h-12h. After the molten salt ion exchange treatment is completed, water washing and drying are performed. The drying temperature is 80°C-150°C, for example, 80°C, 100°C, 120°C, 150°C; the drying time is greater than 12h, for example, 12h, 15h, 20h, 30h, 40h, 50h.

[0078] In some embodiments, after the molten salt ion exchange treatment is completed, the method further includes: mixing with a second lithium source and performing a lithium supplementation treatment.

[0079] By performing lithium replenishment treatment after the molten salt ion exchange treatment, the Li / Co ratio in the lithium cobalt oxide composite material can be increased, thereby ensuring that the lithium cobalt oxide composite material has a high discharge capacity and good cycle stability. When used as a positive electrode material in lithium-ion batteries, it can be used directly without the need for negative electrode lithium replenishment treatment.

[0080] In some embodiments, the second lithium source includes at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium acetate, and lithium hydroxide.

[0081] In some embodiments, the mass concentration of the second lithium source solution is 0.1 g / mL-0.3 g / mL. In some embodiments, the mass concentration of the second lithium source solution is 0.1 g / mL, 0.16 g / mL, 0.2 g / mL, 0.23 g / mL, 0.3 g / mL, or any value between the above adjacent values.

[0082] The alkaline environment provided by the mass concentration of the second lithium source solution in the above range is conducive to the normal lithium replenishment treatment and has less damage to the material.

[0083] In some embodiments, the weight ratio of the O2-phase lithium cobalt oxide material doped with the M element and the second lithium source is (2-20): (10-30). In some embodiments, the weight ratio of the O2-phase lithium cobalt oxide material doped with the M element and the second lithium source is 2:10, 2:20, 2:30, 5:10, 5:20, 5:30, 10:10, 10:15, 10:30, 15:10, 15:20, 15:30, 20:30, or any value between the above adjacent values. The above ratios can provide a suitable lithium concentration difference, which is conducive to the normal progress of the lithium supplementation treatment.

[0084] In some embodiments, the temperature of lithium replenishment treatment is 50°C-95°C, and the time of lithium replenishment treatment is 3h-24h. In some embodiments, the temperature of lithium replenishment treatment is 50°C, 56°C, 67°C, 82°C, 90°C, 95°C, or any value between the above adjacent values. The time of lithium replenishment treatment is 3h, 5h, 10h, 13h, 15h, 18h, 20h, 22h, 24h, or any value between the above adjacent values. The above temperature and time ranges are conducive to the normal progress of lithium replenishment treatment.

[0085] In some embodiments, the lithium supplementation treatment is followed by water washing and drying to obtain an O2 phase lithium cobalt oxide material doped with element M. In some embodiments, the drying temperature is 80°C-150°C, for example, 80°C, 100°C, 120°C, 150°C; the drying time is greater than 12h, for example, 12h, 15h, 20h, 30h, 40h, 50h.

[0086] In some embodiments, the chemical formula of the P2Na precursor is: P2-Na x Co 1-y M y O 2 , where 0.68≤x≤0.75, 0≤y≤0.1, and 0.68≤x / (1-y)≤0.75.

[0087] In some embodiments, the chemical formula of the O2 phase lithium cobalt oxide material doped with M element without lithium supplementation treatment is Li x Na y Co 1-m M m O 2 , where 0.65≤x≤0.80, 0≤y≤1, 0<m≤1, 0.65≤x / (1-m)≤0.80.

[0088] In some embodiments, the chemical formula of the O2 phase lithium cobalt oxide material doped with M element after lithium supplementation is: Li x Na y Co 1-m M mO 2 , where 0.90≤x≤1.0, 0≤y≤1, 0<m≤1, and 0.90≤x / (1-m)≤1.0, for example, the value of x / (1-m) can be 0.91, 0.93, 0.95, 0.97, and 1.0.

[0089] From the general chemical formula of the P2Na precursor and the O2 phase lithium cobalt oxide material doped with the M element, it can be seen that after ion exchange treatment, part of the sodium element in the P2Na precursor is replaced by the lithium element in the first lithium source, and there is also residual sodium element.

[0090] By comparing the chemical formula of O2 phase lithium cobalt oxide material doped with M element before and after lithium supplementation treatment, it can be seen that the molar ratio of lithium element to cobalt element can be increased after lithium supplementation treatment.

[0091] The third aspect of the embodiments of the present application provides a positive electrode sheet, including a positive electrode current collector and a positive electrode active layer stacked and bonded to at least one surface of the positive electrode current collector, the positive electrode active layer includes the lithium cobalt oxide composite material provided in the first aspect of the embodiments of the present application and / or the lithium cobalt oxide composite material prepared by the preparation method of the lithium cobalt oxide composite material provided in the second aspect of the embodiments of the present application.

[0092] The positive electrode sheet provided in the embodiment of the present application has good electrochemical properties, such as a more stable structure and better cycle stability under high voltage, because the lithium cobalt oxide composite material provided in the embodiment of the present application is used as the positive electrode active layer material.

[0093] A fourth aspect of the embodiments of the present application provides a lithium-ion battery, and the lithium-ion battery includes the positive electrode sheet provided in the embodiments of the present application.

[0094] The lithium-ion battery provided in the embodiment of the present application has good electrochemical properties, such as a more stable structure and better cycle stability under high voltage, because it adopts the positive electrode sheet provided in the embodiment of the present application.

[0095] Specific implementation cases

[0096] Example 1

[0097] A lithium cobalt oxide composite material, the chemical formula is: Li 0.96 Na 0.003 Co 0.98 Al 0.04 O 2 The lithium cobalt oxide composite material consists of a core body and a coating layer coated on the core body, the core body is O2 phase lithium cobalt oxide, the O2 phase lithium cobalt oxide is doped with Al element, and the particle size of the core body is 7μm. The coating layer is aluminum oxide, and the thickness of the coating layer is less than 1μm.

[0098] The lithium cobalt oxide composite material is prepared by the following steps:

[0099] (1) Preparation of P2Na precursor: Sodium source (Na 2 CO 3 ), cobalt source (Co 3 O 4 ), M element doping source (Al 2 O 3 ) were uniformly mixed with a Na / Co molar ratio of 0.74 and a Na / Al molar ratio of 1:0.03 and then sintered. The sintering process was specifically carried out by heating the temperature to 800°C at a heating rate of 4°C / min, keeping the temperature for 16 hours, cooling with the furnace, grinding and sieving, and obtaining a P2Na precursor with a chemical formula of Na 0.72 Co 0.98 Al 0.02 O 2 .

[0100] (2) Preparation of an O2-phase lithium cobalt oxide material doped with Al element: The P2Na precursor obtained in step (1) and the first lithium source (lithium nitrate and lithium chloride) are uniformly mixed at a Li / Na molar ratio of 10:1, wherein the molar ratio of lithium nitrate to lithium chloride is 71:29, and then an ion exchange treatment is performed. The ion exchange treatment is specifically performed by heating the temperature to 230°C at a heating rate of 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing with water and drying to obtain an O2-phase lithium cobalt oxide material doped with Al element, the chemical formula of which is Li 0.72 Na 0.003 Co 0.98 Al 0.02 O 2 .

[0101] (3) Preparation of an O2-phase lithium cobalt oxide material doped with Al after lithium supplementation: The O2-phase lithium cobalt oxide material doped with Al obtained in step (2) is uniformly dispersed in deionized water, and a second lithium source (lithium hydroxide) is added, wherein the mass ratio of the O2-phase lithium cobalt oxide material doped with Al, lithium hydroxide and deionized water is 1:2.33:20, and the material is placed in a sealed container, and allowed to stand in an oven at 95°C for 24 hours, and then washed and dried to obtain an O2-phase lithium cobalt oxide material doped with Al after lithium supplementation, and the chemical formula is Li 0.96 Na 0.003 Co 0.98 Al 0.02 O 2 .

[0102] (4) Preparation of lithium cobalt oxide composite material: The O2 phase lithium cobalt oxide material doped with Al obtained in step (3) is mixed with a coating material (Al 2 O 3 )Use planetary stirring vacuum degassing machine to evenly mix and achieve fusion coating treatment, Al 2 O 3The addition amount is 0.4wt%, the speed of fusion coating treatment is 2000r / min, the time is 10min, and the lithium cobalt oxide composite material is obtained, the chemical formula is Li 0.96 Na 0.003 Co 0.98 Al 0.04 O 2 .

[0103] The field emission electron probe microanalysis (CP-EPMA) diagram of the cross section of the lithium cobalt oxide composite material prepared in Example 1 of the present application is as follows: Figure 1 The CP-EPMA diagram of the Al element in the cross section of the lithium cobalt oxide composite material prepared in Example 1 of the present application is shown in FIG. Figure 2 shown.

[0104] Combination Figure 1 and Figure 2 It can be seen that the Al element is coated on the surface of the core particles.

[0105] The XRD pattern of the lithium cobalt oxide composite material prepared in Example 1 of the present application is as follows: Figure 3 As shown on the left, the enlarged image of its characteristic peak is as follows Figure 3 Shown right.

[0106] from Figure 3 It can be seen that the XRD main peak of the lithium cobalt oxide composite material prepared in Example 1 is located at 18.6±0.1°, indicating that the lithium cobalt oxide material used in Example 1 is an O2 phase lithium cobalt oxide material.

[0107] Example 2

[0108] A lithium cobalt oxide composite material, which is different from Example 1 in that: the chemical formula is: Li 0.96 Co 0.98 Al 0.06 O 2 The rest is the same as in the embodiment.

[0109] The lithium cobalt oxide composite material is prepared by the following steps: The difference from Example 1 is that in step (4), Al 2 O 3 The addition amount is increased from 0.4wt% in Example 1 to 0.8wt%, and the rest is the same as Example 1.

[0110] Example 3

[0111] A lithium cobalt oxide composite material, which is different from Example 1 in that: the chemical formula is: Li 0.96 Na 0.003 Co 0.98 Al 0.02 La 0.01 Zr 0.01 O2 , the coating layer is LLZO, and the rest is the same as Example 1.

[0112] The lithium cobalt oxide composite material is prepared by the following steps:

[0113] The difference from Example 1 is: (4) Preparation of lithium cobalt oxide composite material: The O2 phase lithium cobalt oxide material doped with Al element obtained in step (3) is evenly mixed with LLZO by a planetary stirring vacuum degassing machine to achieve fusion coating treatment, and the addition amount of LLZO is 0.3wt%, and the rest is the same as Example 1.

[0114] Example 4

[0115] A lithium cobalt oxide composite material, which is different from Example 1 in that: the chemical formula is: Li 0.96 Na 0.003 Co 0.98 Al 0.03 Ti 0.01 O 2 , the coating layer is LATP, and the rest is the same as Example 1.

[0116] The lithium cobalt oxide composite material is prepared by the following steps:

[0117] The difference from Example 1 is: (4) Preparation of lithium cobalt oxide composite material: The O2 phase lithium cobalt oxide material doped with Al element obtained in step (3) is evenly mixed with LATP by a planetary stirring vacuum degassing machine to achieve fusion coating treatment, and the added amount of LATP is 0.3wt%. The rest is the same as Example 1.

[0118] Example 5

[0119] The preparation steps of the lithium cobalt oxide composite material are different from those of Example 1 in that: in step (4), the rotation speed of the fusion coating treatment is 1500 r / min, the time of the fusion coating treatment is 30 min, and the rest is the same as Example 1.

[0120] Example 6

[0121] The preparation steps of the lithium cobalt oxide composite material are different from those of Example 1 in that: in step (3), the temperature of the lithium replenishment treatment is 75° C., the time of the lithium replenishment treatment is 20 h, and the rest is the same as in Example 1.

[0122] Comparative Example 1

[0123] A lithium cobalt oxide material, which is O3 phase lithium cobalt oxide.

[0124] Lithium cobalt oxide material is prepared by the following steps:

[0125] Li 2 CO 3 and Co 3O 4 The mixture is uniformly mixed with a Li / Co molar ratio of 1.05 and then sintered. The sintering treatment is specifically carried out by heating the temperature to 750°C at a heating rate of 4°C / min, keeping the temperature for 3.5 hours, then heating the temperature to 1000°C at a heating rate of 2°C / min, keeping the temperature for 6.5 hours, cooling with the furnace, grinding and sieving to obtain O3 phase lithium cobalt oxide.

[0126] The obtained O3 phase lithium cobalt oxide material and the coating material (Al 2 O 3 )Use planetary stirring vacuum degassing machine to evenly mix and achieve fusion coating treatment, Al 2 O 3 The addition amount is 0.4wt%, the speed of fusion coating treatment is 2000r / min, the time is 10min, and the lithium cobalt oxide composite material is obtained, the chemical formula is LiCoAl 0.02 O 2

[0127] Comparative Example 2

[0128] A lithium cobalt oxide material is O2 phase lithium cobalt oxide, and the O2 phase lithium cobalt oxide is doped with Al element.

[0129] The lithium cobalt oxide material is prepared by the following steps: The difference from Example 1 is that step (4) is omitted, and what is finally obtained is the O2 phase lithium cobalt oxide material doped with M element after lithium supplementation.

[0130] Performance tests of the products prepared in the examples and comparative examples of the present application:

[0131] The products obtained in Examples 1-6 and Comparative Examples 1-2 were used as positive electrode active materials, conductive carbon black (SuperP) was used as a conductive agent, and polyvinylidene fluoride (PVDF) was used as a binder. The mass ratio of the three was 90:5:5. An appropriate amount of N-methylpyrrolidone (NMP) was added to control the solid content of the slurry to 40%. The slurry was evenly mixed and applied to an aluminum foil current collector. After vacuum drying, the slurry was taken out and hot pressed, and cut into a positive electrode sheet with a diameter of 12 mm and a thickness of about 60 μm. The above-mentioned positive electrode sheet, separator and lithium sheet negative electrode were stacked in sequence, and the electrolyte was injected to assemble a button lithium ion battery.

[0132] The assembled battery was placed in a 45℃ high and low temperature box and subjected to constant current charge and discharge cycle test on the Xinwei battery test channel. The test conditions were: charge and discharge cut-off voltage 3.0-4.65V (vs Li+ / Li), the first cycle charge and discharge rate was 0.1C, the second cycle charge and discharge rate was 0.2C, and the cycle was 50 cycles. The test results are shown in Table 1.

[0133] Table 1 Comparison of electrochemical performance of various examples and comparative examples

[0134]

[0135]

[0136] It can be seen from Examples 1-6 in Table 1 that the embodiments of the present application adopt O2 phase lithium cobalt oxide doped with M element as the core body, combined with the fusion coating treatment, so that an oxide coating layer containing N element can be coated on the surface of the core body. The prepared lithium cobalt oxide composite material not only has good capacity release performance under high potential test, but also has a greatly improved capacity retention rate. Therefore, the lithium cobalt oxide composite material prepared in the embodiments of the present application has good cycle stability under high potential.

[0137] By comparing Example 1 with Comparative Example 1, it can be found that by using O2 phase lithium cobalt oxide to replace the traditional O3 phase lithium cobalt oxide as the core, the capacity retention rate is greatly improved while ensuring the capacity release performance, and the 0.2C initial capacity of the lithium cobalt oxide composite material of Example 1 is improved, thereby improving the rate performance.

[0138] By comparing Example 1 with Example 2, it can be found that by doping the O2 phase lithium cobalt oxide with the M element and combining it with a coating treatment, the capacity retention rate of the lithium cobalt oxide composite material can be significantly improved, and the electrochemical performance of the lithium cobalt oxide composite material is improved.

[0139] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A lithium cobalt oxide composite material, characterized in that: It comprises a core body and a coating layer coated on the core body, wherein the core body comprises O2-phase lithium cobalt oxide, and the O2-phase lithium cobalt oxide is doped with an M element; and the coating layer comprises an oxide containing an N element; The M element includes at least one of Al, Mg, W, Ti, La, Zr, Ni, Mn and Y; The N includes at least one of Al, Mg, Y, W, Nb, La, Zr, Ti and P.

2. The lithium cobalt oxide composite material according to claim 1, characterized in that: The general chemical formula of the lithium cobalt oxide composite material is Li x Na y Co 1-m M m N n O2, wherein 0.9≤x≤1, 0≤y≤0.1, 0<m≤0.1, 0<n≤0.1, and 0.9≤x / (1-m)≤1.

0.

3. The lithium cobalt oxide composite material according to claim 1, characterized in that: The molar ratio of lithium element to cobalt element in the lithium cobalt oxide composite material is 0.9-1.

4. The lithium cobalt oxide composite material according to any one of claims 1 to 3, characterized in that: The main X-ray diffraction peak of the O2 phase lithium cobalt oxide is located at 18.6±0.1°.

5. The lithium cobalt oxide composite material according to any one of claims 1 to 3, characterized in that: The thickness of the coating layer is less than 1 micron; And / or, the particle size of the core body is 5 to 20 microns.

6. A method for preparing a lithium cobalt oxide composite material, characterized in that: include: The O2 phase lithium cobalt oxide material doped with the M element is mixed with the coating material to perform a fusion coating process to obtain a lithium cobalt oxide composite material; wherein, The M element includes at least one of Al, Mg, W, Ti, La, Zr, Ni, Mn and Y; The coating material includes an oxide containing N element, and the N includes at least one of Al, Mg, Y, W, Nb, La, Zr, Ti and P.

7. The preparation method according to claim 6, characterized in that: The coating material comprises at least one of aluminum oxide, magnesium oxide, lithium lanthanum zirconium oxide, lithium lanthanum titanate and lithium aluminum titanium phosphate; And / or, the mass ratio of the coating material to the O2-phase lithium cobalt oxide material containing the M element is (0.2-0.8):100; And / or, the rotation speed of the fusion coating treatment is 1500r / min-5000r / min, and the time of the fusion coating treatment is 5min-30min.

8. The preparation method according to claim 6, characterized in that: The steps for preparing the O2-phase lithium cobalt oxide material doped with the M element include: The sodium source, the cobalt source and the M element doping source are mixed and sintered to obtain a P2Na precursor; The P2Na precursor is mixed with the first lithium source and then subjected to molten salt ion exchange treatment to obtain the O2 phase lithium cobalt oxide material doped with the M element.

9. The preparation method according to claim 8, characterized in that: After the molten salt ion exchange treatment is completed, the process further includes: mixing with a second lithium source and performing lithium supplementation treatment.

10. The preparation method according to claim 9, characterized in that: The second lithium source includes at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium acetate and lithium hydroxide; And / or, the temperature of the lithium supplementation treatment is 50° C.-95° C., and the time of the lithium supplementation treatment is 3 h-24 h.

11. The preparation method according to any one of claims 8 to 10, characterized in that: The sodium source includes at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate; And / or, the cobalt source includes at least one of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt sulfate and cobalt oxyhydroxide; And / or, the M element doping source includes at least one of Al2O3, MgO, WO3, TiO2, La2O3, ZrO2, NiO, MnO2 and Y2O3; And / or, the sintering temperature is 700°C-900°C, and the sintering time is 8h-30h; And / or, the first lithium source includes at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium acetate and lithium hydroxide; And / or, the temperature of the molten salt ion exchange treatment is 180° C.-300° C., and the time of the molten salt ion exchange treatment is 0.5 h-12 h.

12. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active layer laminated and bonded to at least one surface of the positive electrode current collector, wherein the positive electrode active layer comprises the lithium cobalt oxide composite material according to any one of claims 1 to 5 and / or the lithium cobalt oxide composite material prepared by the preparation method according to any one of claims 6 to 11.

13. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet according to claim 12.

Citation Information

Cited By

  • Lithium ion battery

    CN120497324A

  • Composite lithium cobalt oxide positive electrode material, preparation method thereof and lithium ion battery

    CN121076074A

  • O2-phase lithium cobalt oxide positive electrode material and preparation method and application thereof

    CN121134846A

  • O2-phase lithium cobalt oxide positive electrode material and preparation method thereof, secondary battery and electric device

    CN121269822A

  • O2-phase lithium cobalt oxide positive electrode material, preparation method thereof, positive plate and lithium ion battery

    CN121565851A